New teenage challenge: vaping and pregnancy - Mohamed N. Ahmed; Tony Eczema; Nahla Zaghloul (Frontiers in Medicine, 2026)
The use of nicotine and tobacco products in any form is unsafe, and nearly all tobacco product initiation occurs during adolescence. Vaping via electronic cigarettes (ECs) among young individuals remains a major public health concern. According to the 2025 National Youth Tobacco Survey, 5.2% of U.S. middle and high school students currently use ECs (7.1% of high school students and 2.6% of middle school students), making ECs the most consumed tobacco product among youth. While combustible cigarettes deliver high concentrations of carbon monoxide and combustion byproducts, EC aerosol contains variable levels of nicotine alongside chemical toxicants such as formaldehyde, acetaldehyde, nickel, and lead. Systemic nicotine delivery from ECs varies considerably by device design, liquid formulation, power output, and vaping behavior, but can equal or exceed that of conventional cigarettes. Cumulative clinical and epidemiological evidence indicates that exclusive EC use and dual use with combustible cigarettes during pregnancy are associated with adverse perinatal outcomes, including preterm birth and reduced birth weight. This perspective highlights epidemiology, fetal toxicology, adolescent susceptibility, and exposure-specific perinatal outcomes.